Spirulina platensis and Chlorella vulgaris in poultry nutrition - a review of current research and potential opportunities - Sebastian Wlaźlak; Jakub Biesek (Poultry Science, 2025)
Poultry production plays a key role in the global consumer market. One of the most critical factors influencing animal production and welfare is nutrition. In recent years, there has been a noticeable shift towards natural feed additives, especially in response to the ban on antibiotic growth promoters. Among these additives, microalgae, especially Spirulina and Chlorella, have gained attention for their potential nutritional benefits and health-promoting properties. This review examines the research on these microalgae as feed additives in poultry nutrition, with a special focus on their effects on broiler and layer production parameters, including meat and egg quality and the overall health of the birds. The global microalgae market has seen exponential growth, mainly in Asian countries. In Europe, microalgae production remains limited and accounts for less than 1 % of the worldwide output. However, awareness of their health benefits is paving the way for expansion in various applications, including animal nutrition. Spirulina platensis, a cyanobacterium, prospers in alkaline waters and boasts a rich biochemical composition that offers high protein content and essential nutrients beneficial to poultry. Chlorella vulgaris, on the other hand, occurs in freshwater and presents unique nutrient profiles that enhance its usefulness as a feed additive. Literature has shown chiefly the beneficial effects of these microalgae on poultry performance and health status. This review highlights the potential for innovation in poultry farming by incorporating microalgae, which aligns with the growing trend towards natural solutions in animal nutrition. It highlights the need for further research to fully understand their benefits and applications in poultry production, including reproduction.